2013
DOI: 10.4028/www.scientific.net/amm.290.97
|View full text |Cite
|
Sign up to set email alerts
|

Study on Control of the Rotational Speed of Diesel Engine under State-Switch Mode in Parallel Hybrid Hydraulic Excavator

Abstract: In parallel hybrid hydraulic excavator (PHHE) with super capacitor, the throttle position of the diesel engine is changed with the variation of the capacitor’s state of charge (SOC) of the super capacitor. When the throttle position is switched, the rotational speed of the diesel engine cannot be able to increase or decrease to the target speed rapidly enough, and it may fluctuate in large range under given conditions. Under the assumption that the loading torque of the diesel engine is invariant at the switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The schematic diagrams of the traditional power train system and HPTS are presented in Fig. 1 [5][6][7]. The drive torque of a hydraulic pump in a 20-t traditional hydraulic excavator works in typical working cycles is measured and given in Fig.…”
Section: Hybrid Power Train Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The schematic diagrams of the traditional power train system and HPTS are presented in Fig. 1 [5][6][7]. The drive torque of a hydraulic pump in a 20-t traditional hydraulic excavator works in typical working cycles is measured and given in Fig.…”
Section: Hybrid Power Train Systemmentioning
confidence: 99%
“…The maximum output torque of the PMSM can be expressed as where T max is the maximum output torque of the PMSM. According to (7), it can be found that the maximum output torque of the PMSM is mainly decided by the inductance, the maximum allowable current and the amplitude of the rotor magnetic flux linkage vector.…”
Section: Traditional Dtcmentioning
confidence: 99%